2014
DOI: 10.1017/s0963548314000339
|View full text |Cite
|
Sign up to set email alerts
|

Approximately Counting Embeddings into Random Graphs

Abstract: Let H be a graph, and let C_H(G) be the number of (subgraph isomorphic) copies of H contained in a graph G. We investigate the fundamental problem of estimating C_H(G). Previous results cover only a few specific instances of this general problem, for example, the case when H has degree at most one (monomer-dimer problem). In this paper, we present the first general subcase of the subgraph isomorphism counting problem which is almost always efficiently approximable. The results rely on a new graph decomposition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…If the procedure succeeds, we compute the probability with which the clique is obtained in G and output its inverse. As shown in [12], this is an unbiased estimate of the number of cliques in G. We state the results below in Theorem 1. In this work, we generalize Rasmussen's approach [28] to efficiently count k-cliques and k-clique covers in random graphs.…”
Section: Our Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…If the procedure succeeds, we compute the probability with which the clique is obtained in G and output its inverse. As shown in [12], this is an unbiased estimate of the number of cliques in G. We state the results below in Theorem 1. In this work, we generalize Rasmussen's approach [28] to efficiently count k-cliques and k-clique covers in random graphs.…”
Section: Our Resultsmentioning
confidence: 88%
“…Our algorithm is based on the idea of Rasmussen's unbiased estimator for permanents [28]. It has been widely used in the context of subgraph isomorphism counting problems [29,11,12]. For counting k-cliques in the input random graph G, we embed a k-clique into G, doing so one vertex at a time chosen randomly.…”
Section: Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While these approaches are interesting with theoretical guarantees, they apply to specific classes of simple hypergraphs with bounded degree and regularity which cannot model real-world multi-relational data. Fürer and Kasiviswanathan (2014) propose a polynomial time sampling-based approximation strategy for counting isomorphic subgraphs matching a given template leveraging bounded-width ordered bipartite decompositions of the templates. A key feature of this approach is its provable generalization across varied classes of graphs.…”
Section: Background and Related Workmentioning
confidence: 99%
“…E.g. for certain pattern classes, there exist efficient algorithms which provide good approximations on almost all random graphs [31] On the other hand, recent work on fixed parameter tractability has shown that there are algorithms, often randomized ones, whose assymptotic complexity is exponential in the pattern size but only polynomial (e.g. linear) in the network size.…”
Section: Approximative Algorithms For Pattern Matchingmentioning
confidence: 99%